Financial Cryptography and Data Security - Dietrich, Sven (Springer, 2017)
The 11th International Conference on Financial Cryptography and Data Security (FC 2007, http://fc07. ifca. ai), organized by the International Financial Crypt- raphy Association (IFCA, http://www. ifca. ai/), was held in Tobago, February 12–15, 2007. The conference is a well-established and premier international - rum for research, advanced development, education, exploration, and debate - garding security in the context of ?nance and commerce. We continue to cover all aspects of securing transactions and systems, which this year included a range of technical areas such as cryptography, payment systems, anonymity, privacy, - thentication, and commercial and ?nancial transactions. For the ?rst time, there was an adjacent workshop on Usable Security, held after FC 2007 in the same - cation. The papers are included in the last part of this volume. The conference goal was to bring together top cryptographers, data-security specialists, and c- puter scientists with economists, bankers, implementers, and policy makers. The goal was met this year: there were 85 submissions, out of which 17 research papers and 1 system presentation paper were accepted. In addition, the conference featured two distinguished speakers, Mike Bond and Dawn Jutla, and two panel sessions, one on RFID and one on virtual economies. As always, there was the rump session on Tuesday evening, colorful as usual.